1964
DOI: 10.1104/pp.39.4.691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Certain Growth Substances on the Growth and Morphogenesis of Immature Embryos of Capsella in Culture

Abstract: In an earlier paper (7) the development of isolated heart-shaped and older embryos of Capsella4 (> 80 ,u long) when grown in a sterile nutrient medium containing mineral salts, vitamins and 2 % sucrose was described. It was also shown that supplementing the basal medium with a mixture of growth substances like indoleacetic acid (IAA), kinetin and adenine sulfate permitted development of still smaller globular embryos (40-80 ,u walking-stick-shaped (701-1000); inverted-U-shaped (1001-1700) and mature embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…1E). Similar results were reported for other plant species (Beattie andGarrett 1995, Raghavan andTorrey 1964b). In this work, callus formation was also detected in embryos cultured in media containing the highest levels of TDZ, but further embryo development was not observed.…”
Section: Resultssupporting
confidence: 78%
“…1E). Similar results were reported for other plant species (Beattie andGarrett 1995, Raghavan andTorrey 1964b). In this work, callus formation was also detected in embryos cultured in media containing the highest levels of TDZ, but further embryo development was not observed.…”
Section: Resultssupporting
confidence: 78%
“…Since plant growth hormones may also modify membrane permeability (7) and, especially, alter the uptake of other hormones (5), (18); others used kinetin (9). Excised zygotic embryos, especially if immature, profited from either coconut milk (24) or cytokinins (14). However, somatic embryos have been grown in hormone-free media (2) and, as also reported here, cytokinins disrupt their development (8).…”
Section: Discussionmentioning
confidence: 97%
“…However, somatic embryos have been grown in hormone-free media (2) and, as also reported here, cytokinins disrupt their development (8). Gibberellins promoted the development of some excised zygotic embryos (6); with others, it inhibited shoot initiation and promoted root growth (14). ABA has promoted callus formation on Ipomea cotyledons (16) and inhibited callusing of excised immature barley embryos (13).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative measures of each were obtained by combining the results of the Somogyi-Nelson determination of reducing sugar and total sugar with the results of the Glucostat test (Table IV) (17) reported that higher osmolarity was essential for the normal culture of younger embryos of several species. Some disagreement with this finding has been voiced, notably by Raghavan and Torrey (15), but there is some doubt that their Capsella embryos are free of the precocious germination syndrome. Norstog (13) found that high osmolarity was required to prevent the precocious germination of young barley embryos in the dark.…”
Section: Methodsmentioning
confidence: 98%